Performance Effects of Current Consumption on Radio Receiver Bit Error Rate in IEEE 802.15.4 for Wireless Sensor Networks - Bamber, Sukhvinder Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper investigates the radio receiver Bit Error Rate (BER) at different types of devices in IEEE 802.15.4 Wireless Sensor Networks (WSNs) for the different current draw parameters: transmit mode, receive mode, sleep mode and idle mode keeping other parameters like: initial energy and power supply same for all motes; Clearly proving that if BER is to be taken into consideration for the performance enhancement then Z1 mote should be implemented in IEEE 802.15.4 WSNs as they produce minimal BER.Â 